2014
DOI: 10.12681/mms.1041
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of the microbial food web (viruses to ciliates) under the influence of the Black Sea Water inflow (N. Aegean, E. Mediterranean)

Abstract: Τhe entire pelagic microbial food web was studied during the winter-spring period in the frontal area of the North Aegean Sea. Abundance of viruses, heterotrophic bacteria, cyanobacteria, auto- and hetero-trophic flagellates, and ciliates, as well as bacterial production, were measured at three stations (MD1, MD2, MD3) situated along a N-S transect between the area directly influenced by the inflowing Black Sea water and the area covered by the Levantine water. Samples were collected in December 2009, and Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
1
10
0
3
Order By: Relevance
“…The role of food availability for the population increment of C. typicus is also evident from the lower numbers encountered at station MD2 and even less at MD3, as well as from the CCA results, since the species was positively related to chl α. In addition, the availability of ciliates as food declined gradually from MD1 to MD3, especially in the upper layer (Giannakourou et al, 2014). The above observations are in accordance with the statement that C. typicus is not tolerant to starvation (Dagg, 1977).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The role of food availability for the population increment of C. typicus is also evident from the lower numbers encountered at station MD2 and even less at MD3, as well as from the CCA results, since the species was positively related to chl α. In addition, the availability of ciliates as food declined gradually from MD1 to MD3, especially in the upper layer (Giannakourou et al, 2014). The above observations are in accordance with the statement that C. typicus is not tolerant to starvation (Dagg, 1977).…”
Section: Discussionsupporting
confidence: 89%
“…The increased numbers of the herbivore C. helgolandicus among large mesozooplankters at stations MD1 (April and May) and MD2 (April) should be also related to the availability of large diatoms in March (Peliz, 2013) and ciliates in April (Giannakourou et al, 2014). Its absence at station MD3 is most likely due to the paucity of phytoplankton and ciliates (Peliz, 2013;Giannakourou et al, 2014), since it has been found to be abundant in the less oligotrophic regions of the Mediterranean Sea (Bonnet et al, 2005), especially in upwelling and frontal areas (Boucher, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations